Pengaruh Model Problem Based Learning Berbantuan Media Assemblr Edu terhadap Kemampuan Pemecahan Masalah Siswa Kelas V - Putri Novella; Susilawati Susilawati; Djajuli Djajuli (Jurnal Syntax Admiration, 2024)
Problem-solving skills are essential competencies that need to be developed in elementary school students. The application of innovative learning models, such as Problem-Based Learning supported by interactive technology media like Assemblr Edu, can be an effective solution for enhancing these skills. This study aims to analyze the impact of the Problem-Based Learning (PBL) model supported by Assemblr Edu media on the problem-solving abilities of fifth-grade students. The research method used is an experimental method with a Pre-test Post-test Non-Equivalent Control Group Design. The results of the study showed that the use of the PBL model supported by Assemblr Edu significantly improved students' problem-solving abilities compared to conventional learning methods. This can be seen from the significant difference in the N-Gain scores, with the experimental class reaching 0.7 (moderate category) and the control class only 0.2 (low category). These findings suggest that interactive technology media like Assemblr Edu can be an effective tool in enhancing students' critical and analytical thinking skills.